HUBUNGAN MOTIVASI BELAJAR DENGAN KEMAMPUAN BAHASA INGGRIS KELAS VIII DI MTS DAARUSSALAM - Aida Putri, Puput; Isfahani, Rizki (Nusantara Hasana Berdikari, 2022)
The improvement of quality in the field of education is one of the development goals in the field of national education. A person's success in learning can be seen by the changes that occur in a person in attitudes, thinking abilities, and skills. In an effort to keep pace with the development of science and technology, English has now become one of the lessons that must be mastered by students. The research is quantitative with an analytical research design using the populan cross sectional method as many as 149 and the number of samples used. using namus sobin as 109 people.. The results of the analysis using chi square with a p value was 0.000 <0.05,so it can be concluded that there is a relationship between learning motivation and English language skills. Â